E-057 Admission CT perfusion may underestimate initial infarct core in isolated deep middle cerebral artery strokes. (22nd July 2019) - Bouslama, M; Ravindran, K; Rodrigues, G; Pisani, L; Haussen, D; Barreira, C; Frankel, M; Nogueira, R
Abstract : Background and purpose: Proper identification of infarct core is crucial in establishing stroke prognosis and determining whether a patient might be a candidate for endovascular therapy (ET). We sought to study those cases in which admission CTP misses a core lesion that is present on initial non-contrast CT. Methods: Review of a prospectively collected database of endovascular patients with anterior circulation Large vessel occlusion strokes from January 2014-November 2018. Only patients with an e-ASPECT score <10 and adequate CTP maps were included. A Total Missed infarct Core (TMC) was defined as a CTP core lesion (rCBF<30%) <1 cc with a visualized hypodensity on initial non-contrast CT. Results: 629 patients qualified for the study. Median age was 64 [54–75], median NIHSS was 16 [12.5–21] and median time from last-known normal to CT was 317 mins [193–578]. 161 (25.6%) presented with a TMC. On univariate analysis a TMC was associated with isolated deep MCA strokes (77.6% vs 56.6%, p<0.001) and higher collateral scores (3[2–3] vs 2[1–3], p<0.001). There were no differences between patients presenting with a TMC and others in good outcomes (mRS 0–2) (50.8% vs 47.6%, p=0.53) or 90-day mortality (23% vs 17.6%, p=0.17) while TMC patients had lower rates of any parenchymal hematomas (5.2% vs 14.6%, p=0.02). After adjusting for potential confounders, isolated deep MCA strokes was identified as an independent predictor of TMC (OR 2.49 95%CI 1.63–3.8, p<0.001). Conclusions: Our results show that CT perfusion might miss infarct core in 25% of the case, especially in isolated deep MCA strokes. In those cases, a CT Perfusion based paradigm to determine eligibility for ET might not be as accurate. Future studies looking into the optimal selection tools for this patient population as well as refinements of the post-processing algorithms addressing this pitfall are warranted. Disclosures: M. Bouslama: None. K. Ravindran: None. G. Rodrigues: None. L. Pisani: None. D. Haussen: None. C. Barreira: None. M. Frankel: None. R. Nogueira: 2; C; Stryker Neurovascular (Trevo-2 Trial PI - modest, DAWN Trial PI – no payment, Trevo Registry Steering Committee – no payment, Physician Advisory Board/Consultant - significant), Covidien/Medtronic (SWIFT and SWIFT-PRIME Steering Committee - modest, STAR Trial Core Lab - significant), Neuravi/Cerenovus (ARISE-II Trial Steering Committee – no payment, Physician Advisory Board - modest), Phenox (Physician Advisory Board/Consultant – modest), Genentech (Physician Advisory Board/Consultant – modest). 6; C; Penumbra (3-D Separator Trial Executive Committee – no payment).